Romanian Presidential Institution in the Present Constitutional Framework - Cristian Ionescu (Sfera Politicii, 2012)
Romanian semi-presidential system, and the Republic President`s role within government process represent a very actual theme for political sciences and both for constitutional doctrine. Constitution adopted in 1991 and revised in 2003, had consecrated the model of semi-presidentialism but did not manage to find for the President of the Republic the suitable prerogatives to his constitutional role. President of Romania has attributions of a president in a parliamentary republic but often the will and power claims of presidents exceeded their constitutional role. In this way, the President step in disputes both with Parliament and Government. In this article, the author focuses on the institutional relationships between President, Parliament and Prime Minister and the Presidential legitimacy, also.